The Importance of Science and Education in the Period of Amir Temur and Temurids in Increasing the Sense of Patriotism in Young People - Jahongirovich, Ibragimov Anvarjon (European Journal of Life Safety and Stability (2660-9630), 2022)
This article shows the great influence of Sihibkiran Aimir Temur on the economic and cultural development of our ancestor, the development of science, literature and art, handicrafts and architecture, as well as the wise ideas of scholars on morality and aesthetics. in enriching them, in educating them in the spirit of high moral qualities.